Pengaruh Anemia Pada Ibu Hamil Dengan Kejadian Berat Badan Lahir Rendah Di Puskesmas Ngegong - Ambarwati, Sri; Suparji, Suparji; Nuryani, Nuryani (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2023)
ABSTRACT Low Birth Weight Infants remain a major cause of infant mortality and morbidity, and a problem in the care of pregnant women worldwide, especially in developing countries. Anemia in pregnant women is one of the causes of high LBW rates. The purpose of this study was to determine the effect of anemia on pregnant women with low birth weight events at the Ngegong Health Center in 2022.This research is an analytical research that is cross sectional. Samples were taken using the Proportionate simple random sampling technique of 163 pregnant women. The independent variable in this study was anemia in pregnant women, while the dependent variable in this study was LBW. Data collection used a documentation study, namely the cohort of pregnant women and infants in 2022. To analyze the effect, the Spearman Rank test was used with a significance of α = 0.05.The results showed that almost all pregnant women (76.7%) at the Ngegong Health Center in Madiun City did not experience anemia. Almost all pregnant women (84.7%) at the Ngegong Health Center in Madiun City gave birth to babies who were not LBW. From the results of the Spearman Rank test, it was concluded that there is an effect of anemia on pregnant women with low birth weight events.Suggestions for health workers at the Puskesmas to provide counseling on how to take fe tablets properly and correctly and monitor pregnant women to regularly take Fe tablets, and provide counseling about danger signs to pregnant women